“To Collect Information, Not to Deduce Law”: Al-Biqāʿī’s (d. 1480) Argument for Interpreting the Quran with the Bible - Muchlisin, Annas Rolli (Universitas Islam Internasional Indonesia, 2024)
This paper investigates how premodern Muslim intellectuals understood and utilized Biblical materials in their written works. While some studies have highlighted Muslim use of the Bible for polemical and apologetic purposes, this study shows that medieval Muslim interaction with Biblical passages was not confined to those two approaches, illustrating the complexity of their engagement with the Bible. Taking the fifteenth-century Mamluk Quran commentator Burhān al-Dīn al-Biqāʿī (d. 1480) as a case study, this paper discusses how al-Biqāʿī sought to quote relevant Biblical passages to offer a more comprehensive narrative of figures and events mentioned only briefly in the Quran. Criticized by his contemporaries, al-Biqāʿī wrote his Apologia to defend his approaches. Analyzing al-Biqāʿī’s Apologia reveals the central argument that, for him, interpreting the Quran with the Bible is permissible for narrative and admonitory purposes but not for determining articles of faith and Islamic laws. In the end, he underscores the significant difference between taḥrīf (falsification) and naskh (abrogation), which should be appropriately understood in dealing with pre-Islamic revelation. Although he implied that certain Biblical passages were safe from textual falsification based on their conformity with the Quran, he supported the concept of abrogation, a widespread idea in medieval times across various religious traditions.